“LEXICAL – SEMANTIC FIELD OF THE WORDS DENOTING “APPEARANCE” - Abdullayeva , Aziza Umidullayeva (Educational Research in Universal Sciences, 2023)
This paper explores the link between word semantics and coherence through combinatorial semasiology. A word’s cognate, which is a crucially accurate linguistic indicator of its meaning, determines how it joins with another word in a particular sense. There is discussion and illustration of the semantic structure of words connected to appearance in English. Additionally, this essay studies various approaches to word semantics.